Myths and realities of digital reference services : Perspectives of libraries from developing countries / Ahmad Bakeri Abu Bakar - Abu Bakar, Ahmad Bakeri (2011)
With the increasing availability of electronic information services and the emergence of the Web the notion of traditional reference services has been altered. Libraries in the US have begun to offer Web–based reference services which are termed ―digital‖ or ―virtual‖ reference services and those in other countries such as UK are following suit. This paper aims to determine whether developing countries in Asia and Pacific region have caught up yet with the realities of offering digital reference services in real time with a 24/7 operating mode. To what extent has this phenomenal change affecting reference services gripped the libraries of developing countries? Do developing countries in the Asia and Pacific region are implementing the digital reference services in their libraries like what is happening in the developed countries? In order to address this issue a survey of the current practices related to reference services in libraries of developing countries in the Asia and Pacific region was studied. Data for this study were gathered from selected academic libraries websites located in the region. The levels of reference services are judged using a scale that measures their maturity. A library that operates traditional services where a user is provided with answers through personal contact, normal mail, or telephone is treated as having zero maturity. A score of 1 is assigned to a country when libraries have begun providing email reference. An email link on the library website is an indicator of this level of virtual reference service. A score of 2 is assigned to a country in which libraries are providing email reference together with a web form, while a score of 3 is assigned to a country when libraries are using a web form together with online chat. When libraries have a web form, online chat and other mode of online communication designed solely for reference service, a score of 4 is assigned. A score of 5 is assigned to a country where their libraries offer digital reference services in real time with 24/7 operating mode. The findings showed that not a single country in the Asia and Pacific region was able to offer virtual reference services in real time on a 24/7 basis. Some of the academic libraries offering virtual reference services have online chat but for a limited time only as shown in the case of academic libraries of the Philippines. Keywords: digital reference services; developing countries; traditional reference services; digital libraries; evaluation.